Preparation and Study Some Physical Properties of (CMC/PAA: MgO) Nano Composites - Halah M HUSSEIN; M. H. Al-Timimi (Genius Journals, 2022)
Pure polymeric films (CMC/PAA) prepared by solution casting method (solution casting) and reinforced with magnesium oxide particles (MgONPs) by Precipitation method with different weight ratios (0, 3, 5, and 7) wt%, Calcined at different temperatures (800°C). The results of Electron microscopy (SEM) reveal that the polymeric film (CMC/PAA) appears to be homogeneous and interconnected and, when applied )CMC/PAA:MgO 7%), forms well-dispersed aggregates in the nanocomposites films. (FTIR) the spectrum revealed that (MgONPs) does not have a destructive effect on the polymer structure as there are no covalent bonds between (CMC, PAA, and MgONPs). The optical properties of the nanocomposites )CMC/PAA:MgO) were measured in the wavelength range (200- 1000) nm. The optical results showed that by increasing the nanomaterial concentration, the (reflectance, absorption coefficient, reflection index, extinction coefficient, and the real and imaginary dielectric constant) increased while the transmittance and energy gap decreased. The results show that the thermal conductivity coefficient (K) is significantly increased when magnesium oxide nanoparticles (MgONPs) are added to the polymeric mixture, and this increase in the thermal conductivity coefficient is a result of filling the polymer with nanoparticles
Keywords: CMC; PAA; MgONPs; Structural properties